Penguatan Kapasitas Kepemimpinan Institusional Dalam Transformasi Administrasi Negara Guna Meningkatkan Daya Saing Nasional - Fernanda, Desi (Pusjar SKPP Lembaga Administrasi Negara, 2007)
During new order regime, indonesia has exprienced both state failures and market failures which, fortunately, inspiring the emergence of civil society movement.